Compliance of Boiler Standards and Industrial Safety in Indian Subcontinent (International Journal of Engineering Materials and Manufacture, 2018)
The economic development and industrialisation necessitate the use boilers/pressure vessels. With the increase of boiler numbers and uses, the boiler explosion due to non-compliance of standards and regulations, poor operation, maintenance, repair and safety awareness is also growing. Human error and poor maintenance are responsible nearly 50% of the global boiler explosions. The fatalities due to boiler explosions are sky rocketing in the Indian subcontinent. The paper has reviewed the global boiler explosions fatalities with a special emphasis on boiler accidents occurred in the Indian subcontinent and suggested some remedial actions.